The Effect of Applying Venn Diagram Strategy on Students’ Achievement in Reading Comprehension at the Twelfth Grade Students of SMK N 5 Medan - Lastri Wahyuni Manurung; Fernando Saragih; Christina Natalina Saragi; Listra Manurung (Sean Institute, 2022)
This research is intended to find out whether Venn diagram Strategy significantly Affects the students’ achievement in reading comprehension or not. In this thesis, the writer conducted experimental quantitative research. The population of this research was the twelve grade of SMK N 5 Medan. The samples of this research were two classes, which were selected by the technique of sample Cluster in random sampling. They were 48 students. The first class was 24 students of the experimental class who had been taught by Venn Diagram Strategy and the second one was 24 students of the control group who had been taught by conventional Strategy. The instrument for collecting the data was multiple choice testing. To obtain the reliability of the test, Kuder Richardson Formula (KR-21) was used. The calculation showed that the reliability of the test was 0.92. The data were analyzed by using the t-test formula in order to see whether Venn Diagram Strategy significantly effect students’ reading comprehension or not. The finding indicates that the value of the t-test exceeds the value of the t-table (3.07> 1.67866), at the level of significant p= 0.05 and the degree freedom df= 46. The finding implies that the alternative hypothesis is accepted. In other words, there is a significant effect of applying the Venn Diagram Strategy on the students’ Achievement in reading comprehension.